PERKEMBANGAN SIPAS KOMIK SEBAGAI UPAYA PENINGKATAN LITERASI BACA DI SEKOLAH DASAR - Mita Aswatun; Muliani; Miftahul Jannah 74; Miftahul Jannah 75; Syafruddin Muhdar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The low reading literacy ability of elementary school students in Indonesia remains a major challenge, especially in the learning of Natural and Social Sciences (IPAS), which is still dominated by the use of conventional media with less variety. This study aims to produce SIPAS Comics as an innovative learning media to improve the reading literacy of elementary school students. The study applies the Research and Development (R&D) method with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The subjects of the study were third-grade students of SD Negeri 35 Ampenan. Data collection techniques included observation, interviews, validation questionnaires, and pre-test and post-test tests. The results showed that SIPAS Comics obtained a very feasible category based on validation by material experts of 93.3%, media experts 90%, and language experts 94.4%. Product implementation showed a high level of practicality in learning. The effectiveness test showed an N-Gain value of 82.5% in the limited test and 76.28% in the experimental class with a high category. These results demonstrate that SIPAS Comics is effective in improving students' reading literacy through the presentation of contextual, visual, and appropriate science and science materials tailored to the characteristics of elementary school students. SIPAS Comics can be used as an alternative, innovative learning medium to support the continuous strengthening of reading literacy.